Pragmatic Equivalence of Expressive Speech Act in Television Series Bridgerton - Darmawati, Dwita; Sajarwa, Sajarwa (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2022)
This article aims to identify pragmatic equivalence in the translation of expressive speech acts. Descriptive and comparative methods were used in this study to analyze the data. Data collection is done by analyzing documents with the technique of observing and note-taking. The data is in the form of utterances containing expressive speech acts on the subtitles of the Bridgerton TV series in English and Indonesian. The data is obtained through accessing the Netflix platform with a personal account. Found 123 data of expressive speech acts on the Bridgerton TV series subtitle with the functions of criticizing, praising, sarcastic, complaining, apologizing, condolences and thanks. The result of the research shows that there are two types of pragmatic equivalence that the Bridgerton TV series subtitle translator has successfully achieved in translating expressive speech acts. The equivalences are the equivalence of expressive illocutionary force and the equivalence of the distance of relevance. Thus, the translator has been able to convey messages from the source text to the target text commensurately.